Adapting livestock water productivity to climate change - Haileslassie, Amare; Blümmel, Michael; Clement, Floriane; Ishaq, S.; Khan, M.A. (Emerald Publishing Limited, 2011)
Purpose – The main purposes of this paper were to assess effects of smallholder farmers access to livelihood capital (e.g. land, livestock and water) on livestock water productivity (LWP) and to evaluate impacts of selected interventions in reducing livestock water demand (per unit of livestock product) and therefore increasing LWP. Design/methodology/approach – A total of 203 sample farm households were selected in intensive and semi-intensive crop-livestock systems of Indo-Ganga basin of India. A household survey was undertaken to capture data on land, water and livestock management. For the analysis, sample farms were clustered into poor, medium, better-off. LWP is estimated as a ratio of livestock beneficial-outputs (e.g. milk) to depleted-water (i.e. evapotranspired water to produce livestock feed). Impacts of selected interventions, on LWP, were analyzed using scenarios developed on a spread sheet model. Findings – The results showed different LWP values among farm-clusters and levels of intensification. The intensive systems showed higher LWP than the semi-intensive. In the baseline, dairy water demand to produce a liter of milk was higher than the world average: ranging between 1,000 and 29,000?L. Among the farm-clusters, variation of LWP was system specific and affected by farmers' access to virtual water trading (i.e. milk and feed). Improving milk productivity, feed quality and feed water productivity reduced livestock water demand per liter of milk substantially and, therefore, the saved water can be used to augment ecosystem services that can mitigate the impacts of climate change. Originality/value – This paper revealed that in the study systems LWP, in the business as usual scenario, is low. But by improving animal productivity, quality feed supply and water conservation substantial volume of water can be saved.